A review on house design with energy saving system in the UK. (May 2017) - Xie, Y.; Gilmour, M.S.; Yuan, Y.; Jin, H.; Wu, H.
Abstract: As part of EU incentives, the UK government have set ambitious environmental targets relating to energy consumption including a reduction of carbon emissions of 80% by 2050. The use of various technologies can help meet these targets as well as providing a secure energy source for the UK in the future. This research took the UK as a case study and investigated where reduction measures are most suited to reduce energy consumption. This paper presents a review on the current state-of-the-art on the domestic technology available, in particular solar energy, heat pumps, phase changing materials (PCMs) and micro combined heat and power (micro-CHP) systems, aiming at identifying research and development opportunities for energy saving in these fields. Furthermore, the financial as well as environmental aspects are assessed as these are the two key considerations of typical household. A typical UK house design, including the floor plan, is created through the use of computer aided design (CAD) software. The house design gives a payback period between 8.7 years at best and 11.6 years at worst.